A Systematic Review of Sustainable Agriculture Practices: Evaluating Environmental and Economic Impacts - Mappigau, Ernawaty (Penelitian dan Pengembangan Ilmu, 2024)
No-till farming offers a variety of environmental benefits but faces challenges in terms of efficiency and economic sustainability. This research aims to explore the role of technological innovation in improving efficiency and economic sustainability in no-till farming practices through a systematic review of the literature. The research results show that the adoption of technologies such as no-till planting machines, soil sensors, and digital monitoring systems can increase productivity, reduce operational costs, and improve the quality of crop yields, thereby supporting long-term economic sustainability. These findings imply the need for policy support and training to overcome initial barriers to technology investment and promote more efficient and sustainable agricultural practices.